THE INFLUENCE OF THE APPLICATION OF INFORMATION TECHNOLOGY ON THE OLD KITCHEN CULINARY BUSINESS - Meriza, Mica Siar; Daole, Adel Syesaria Agustina; Selpiana, Selpiana; Purba, Ledi Marina; Purba, Ellyka Evitasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of information technology implementation on the culinary business Dapur Lama. Dapur Lama, which was founded in October 2023 by Suci Sartika, has experienced significant development thanks to the use of information technology. Through in-depth interviews, this study identified various technologies implemented, such as digital cashier systems, social media, and online ordering applications, as well as their impact on operational efficiency, increasing the number of customers, and service quality. The results of the interviews showed that the implementation of information technology not only improves operational efficiency, but also expands market reach and increases customer satisfaction. Although there are challenges in managing technology and content consistency, the benefits obtained are much greater. This study concludes that information technology plays an important role in the development of culinary businesses in the future and provides recommendations for other business actors to gradually implement relevant technology